Rancang Bangun Alat Pendeteksi Kebakaran Berbasis Iot (Internet Of Things) Dengan Sensor Asap Dan Api - Zaki Hamam Ababil; Muhammad Cordiaz (CV. Shofanah Media Berkah, 2023)
A disaster is an event or series of events that can threaten safety and harm someone who experiences it, which is caused by natural and non-natural factors such as humans so that it can result in environmental damage, loss of property, trauma, and even loss of life. One of the disasters that occurs quite frequently is fire. The common cause of fires is that they can be caused by nature (forest fires due to wood rubbing against each other, lightning strikes, volcanic eruptions, etc.). The aim of this research is to minimize losses caused by fire by designing an Internet of Things-based fire detection system. This research uses a data source collection method using a literature study method by collecting references taken from various literature related to the research title and the waterfall method as a system development method by going through several stages such as Requirement Analysis, System and Software Design, Implementation and Unit Testing, Integration and System Testing, Operation and Maintenance. The results of this research show that this Internet of Things-based fire detection tool uses two sensors, namely a fire sensor which can detect the presence of fire and the MQ-2 smoke sensor which can detect when there is smoke that has the potential to cause a fire. When the device detects fire or smoke, the buzzer on the detection device will sound, then the device will send a fire danger message via the Telegram application and can monitor the condition of the sensors on the device via the fire detection system website.